Canonical Signal Recognition Particle Components Can Be Bypassed for Posttranslational Protein Targeting in Chloroplasts - Tzvetkova-Chevolleau, Tzvetelina (American Society of Plant Biologists, 2007)
The chloroplast signal recognition particle (cpSRP) and its receptor (cpFtsY) target proteins both cotranslationally and posttranslationally to the thylakoids. This dual function enables cpSRP to utilize its posttranslational activities for targeting a family of nucleus-encoded light-harvesting chlorophyll binding proteins (LHCPs), the most abundant membrane proteins in plants. Previous in vitro experiments indicated an absolute requirement for all cpSRP pathway soluble components. In agreement, a cpFtsY mutant in Arabidopsis thaliana exhibits a severe chlorotic phenotype resulting from a massive loss of LHCPs. Surprisingly, a double mutant, cpftsy cpsrp54, recovers to a great extent from the chlorotic cpftsy phenotype. This establishes that in plants, a new alternative pathway exists that can bypass cpSRP posttranslational targeting activities. Using a mutant form of cpSRP43 that is unable to assemble with cpSRP54, we complemented the cpSRP43-deficient mutant and found that this subunit is required for the alternative pathway. Along with the ability of cpSRP43 alone to bind the ALBINO3 translocase required for LHCP integration, our results indicate that cpSRP43 has developed features to function independently of cpSRP54/cpFtsY in targeting LHCPs to the thylakoid membranes.